Determinants of severe acute malnutrition among under-five children in Ethiopia: analysis using data from the 2016 Ethiopia Demographic and Health Survey - Areba, Abriham Shiferaw; Abame, Desta Erkalo; Tirore, Lire Lemma; Bubamo, Bisrat Feleke (Frontiers in Nutrition, 2024)
Objective Malnutrition is a silent killer that is under-reported, under-addressed, and, as a result, emphasized. This study aimed to identify the determinants of severe acute malnutrition (SAM) among under-five children in Ethiopia. Methods Cross-sectional data from the 2016 Ethiopian Demographic and Health Survey (EDHS) were used. A total of 6,170 under-five children were included in the current analysis. The data were cleaned and analyzed using STATA 14. An adjusted odds ratio (AOR) and their 95% confidence intervals (CIs) were calculated to determine the association between factors and outcomes. A p-value of less than 0.05 was considered significant in multivariable logistic regression. Results A multivariable logistic regression revealed that under-five children with the age of children in months 6–11 (AOR = 1.52, 95% CI: 1.25, 1.86), 12–23 (AOR = 1.98, 95% CI: 1.65, 2.37), and 24–59 months (AOR = 1.71, 95% CI: 1.40, 2.08), birth order between fourth and fifth (AOR = 1.24, 95% CI: 1.01, 1.54), having fever (AOR = 1.31, 95% CI: 1.09, 1.58), anemic children (AOR = 1.21, 95% CI: 1.07, 1.36), age of mothers in years 25–34 (AOR = 0.60, 95% CI: 0.51, 0.72) and 35–49 (AOR = 0.49, 95% CI: 0.39, 0.63), antenatal care (ANC) visits (AOR = 0.83, 95% CI: 0.71, 0.92), rural residence (AOR = 2.98, 95% CI: 2.54, 3.49), and solid fuels users (AOR = 2.46, 95% CI: 1.86, 3.26) were significant predictors. Conclusion Older age of children, those with higher birth order, those having fever, anemic children, those living in rural areas, and solid fuel users were more likely to suffer from SAM, while older mothers and those having ANC visits had reduced SAM as significant predictors.